DISPARITIES OF PUNISHMENT AGAINST PEOPLE OF THE CRIME OF ABORTION (Analysis Decision Number 01/ Pid.B /2013/ PN.Plp and Decision Number 242/ Pid.Sus /2015/ PN.Kpg ) - Muhammad Rafandi Harahap; Andry Syafrizal Tanjung; Mhd Azhali Siregar (PT. Radja Intercontinental Publishing, 2024)
Various form problems that occur in handling case follow criminal abortion that is exists disparity criminal in matter his punishment . Problem the the source is judge's decision . Power judiciary as something free and independent state power in one side bring huge impact​ positive to effort enforcement law in Indonesia. Writing This use study law descriptive , which is in study This writer use type study juridical normative use method Research data collection References . Study This For know How accountability criminal to perpetrator follow criminal abortion , implementation law to perpetrator follow criminal abortion , in analysis decision number : 01/ Pid.B /2013/ PN.Plp and decision number : 242/ Pid.Sus /2015/ PN.Kpg . Based on results research and discussion then get it picture , that accountability criminal perpetrator do follow criminal abortion arranged in Articles 299, 346-349 of the Criminal Code and regulated in Articles 75-77 and Article 194 of the Law Number 36 of 2009 Concerning Health . Application law to the perpetrator did it follow criminal abortion analysis decision Number 01/ Pid.B /2013/ PN.Plp and Number 242/ Pid.Sus /2015/ PN.Kpg , that before drop criminal to the defendant , the judge has base considered considerations​ from charges and facts at trial . Analysis decision Palopo District Court Already in accordance with the elements charged prosecutor prosecutor general which the judge decides with based charges and facts at trial , vs backwards with the Kupang District Court The Panel of Judges did not consider indictment prosecutor prosecutor second general​ that is elements chapter more dominant proven inside​ facts the judge Because perpetrator abortion No is from power medical or power health so that give rise to oddity rule law in the position process applied law​ to perpetrator follow criminal different abortions​ to two decision perpetrator follow criminal abortion .